The determination of audit quality in the property sector - Indah Anggraeni, Rahayu; Indra Purnama, Yunus; Junaidi, Junaidi (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
Audit quality remains a persistent concern in Indonesia, particularly due to recurring instances of financial statement manipulation that often go undetected by auditors. These manipulations highlight the urgency of understanding the key determinants influencing audit quality. The COVID-19 pandemic, which began in early 2020, exacerbated these issues, particularly in the property and real estate sectors, which experienced a sharp decline in demand and, in many instances, received going-concern audit opinions. This research examines how variations in CPA firm size, audit fees, firm size, and the length of the auditor engagement influence audit quality. Using a quantitative research approach, data were collected from secondary sources, including audited financial statements, audit reports, and annual reports of property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A purposive sampling method was used to select 31 firms, yielding 155 firm-year observations. Hypotheses were tested using descriptive statistics and logistic regression. The findings show that larger audit firms are associated with higher audit quality, whereas higher audit fees are associated with lower audit quality. Meanwhile, company size and audit tenure do not have a significant impact on audit quality. The results of this research enrich discussions regarding the factors that shape audit quality in developing economies and provide actionable insights for regulators, audit practitioners, and governance actors to enhance monitoring mechanisms and promote greater transparency